2019
DOI: 10.1111/ele.13275
|View full text |Cite
|
Sign up to set email alerts
|

Survival costs of reproduction are mediated by parasite infection in wild Soay sheep

Abstract: A trade‐off between current and future fitness potentially explains variation in life‐history strategies. A proposed mechanism behind this is parasite‐mediated reproductive costs: individuals that allocate more resources to reproduction have fewer to allocate to defence against parasites, reducing future fitness. We examined how reproduction influenced faecal egg counts (FEC) of strongyle nematodes using data collected between 1989 and 2008 from a wild population of Soay sheep in the St. Kilda archipelago, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 77 publications
6
42
0
Order By: Relevance
“…Our analyses revealed that changes in FEC across the season were influenced by reproductive effort: females that reproduced (Figure , Supporting Information Table S1) and those that produced heavier litters (Figure b, Supporting Information Table S2) exhibited steeper rises in FEC across the season. These observations mirror the reproduction‐induced increase in parasite burden exhibited in many studies previously, including in Soays (Leivesley et al, ), bighorn sheep Ovis canadensis (Festa‐Bianchet, ), domestic sheep (Beasley et al, ) and other wild vertebrates (East et al, ; Knowles et al, ; Nordling et al, ). These results could potentially be attributed to two mechanisms: a cost of reproduction, in the form of fewer resources remaining for allocation to immune‐mediated parasite resistance (Sheldon & Verhulst, ), or an increase in exposure across the season as hungry females spend more time foraging in nutrient‐rich, but also parasite‐rich tussock vegetation (Hutchings, Milner, Gordon, Kyriazakis, & Jackson, ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our analyses revealed that changes in FEC across the season were influenced by reproductive effort: females that reproduced (Figure , Supporting Information Table S1) and those that produced heavier litters (Figure b, Supporting Information Table S2) exhibited steeper rises in FEC across the season. These observations mirror the reproduction‐induced increase in parasite burden exhibited in many studies previously, including in Soays (Leivesley et al, ), bighorn sheep Ovis canadensis (Festa‐Bianchet, ), domestic sheep (Beasley et al, ) and other wild vertebrates (East et al, ; Knowles et al, ; Nordling et al, ). These results could potentially be attributed to two mechanisms: a cost of reproduction, in the form of fewer resources remaining for allocation to immune‐mediated parasite resistance (Sheldon & Verhulst, ), or an increase in exposure across the season as hungry females spend more time foraging in nutrient‐rich, but also parasite‐rich tussock vegetation (Hutchings, Milner, Gordon, Kyriazakis, & Jackson, ).…”
Section: Discussionsupporting
confidence: 80%
“…Our analyses revealed that changes in FEC across the season were influenced by reproductive effort: females that reproduced ( Figure 3, Supporting Information Table S1) and those that produced heavier litters (Figure 2b, Supporting Information Table S2) exhibited steeper rises in FEC across the season. These observations mirror the reproduction-induced increase in parasite burden exhibited in many studies previously, including in Soays (Leivesley et al, 2019), bighorn sheep Ovis canadensis (Festa-Bianchet, 1989), domestic…”
Section: We Examined Between-individual Variation In Fec Within a 4-supporting
confidence: 88%
See 2 more Smart Citations
“…The deer are not amenable to experimental manipulation, but they are censused regularly, providing detailed information on their survival and reproductive success (Clutton-Brock et al ., 1982). In such situations, path analysis can be used to infer links between parasites and their fitness consequences (Pacejka et al ., 1998; Stjernman et al ., 2004; Brambilla et al ., 2015; Leivesley et al ., 2019). Notably, a recent analysis in a wild population of Soay sheep used path analysis to demonstrate that reproduction reduced survival through increased parasite intensity and reduced body weight (Leivesley et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%